Miss Fisher & the crypt of tears [videorecording (DVD)] - Davis, Essie; Page, Nathan, 1973-; Naga, Khaled Abol; Margolyes, Miriam; Penry-Jones, Rupert, 1970-; Greenwood, Kerry (RLJ Entertainment, 2020)
Glamorous lady detective Phryne Fisher returns in a cinematic sequel to the wildly popular TV series. In 1929 Jerusalem, Phryne's rescue of a young Bedouin girl leads her on a globe-trotting adventure to uncover priceless treasures, wartime secrets, and an ancient tomb bearing a terrible curse, with the help of handsome detective Jack Robinson.